Nonobese mice with nonalcoholic steatohepatitis fed on a choline‐deficient, l‐amino acid‐defined, high‐fat diet exhibit alterations in signaling pathways - Noriko Suzuki‐Kemuriyama; Akari Abe; Sae Nakane; Kinuko Uno; Shuji Ogawa; Atsushi Watanabe; Ryuhei Sano; Megumi Yuki; Katsuhiro Miyajima; Dai Nakae (FEBS Open Bio, 2021)
Nonalcoholic steatohepatitis (NASH) is often associated with obesity, but some patients develop NASH without obesity. The physiological processes by which nonobese patients develop NASH and cirrhosis have not yet been determined. Here, we analyzed the effects of dietary methionine content on NASH induced in mice fed on a choline‐deficient, methionine‐lowered, l‐amino acid‐defined high‐fat diet (CDAHFD). CDAHFD with insufficient methionine induced insulin sensitivity and enhanced NASH pathology, but without obesity. In contrast, CDAHFD with sufficient methionine induced steatosis, and unlike CDAHFD with insufficient methionine, also induced obesity and insulin resistance. Gene profile analysis revealed that the disease severity in CDAHFD may partially be due to upregulation of the Rho family GTPases pathway and mitochondrial and nuclear receptor signal dysfunction. The signaling factors/pathways detected in this study may assist in future study of NASH regulation, especially its ‘nonobese’ subtype.